Identification of the Aquifer Occurrences in Sungai Raya and Its Surroundings, Bengkayang, West Kalimantan - Cakrabuana, Wira; Fauzi, Rachman; Karunianto, Adhika Junara; Muhammad, Adi Gunawan; Widodo, Widodo (Jurnal Lingkungan dan Bencana Geologi, 2022)
A hydrogeological study was carried out in Sungai Raya Village, Bengkayang Regency, West Kalimantan Province. The objectives of the study were to identify the occurrences of the aquifer in Sungai Raya, along with its type, depth, distribution, and quality. The methods used in this study were literature studies of geological data and geoelectrical measurement. Based on the literature study, it was known that the study area, from the oldest to the youngest, consists of andesite, granodiorite, diorite, quartz sand deposit, littoral deposit, and alluvial deposit. Based on the geoelectrical measurement, it resulted that most of the subsurface layers recorded by the instrument are alluvial deposit (characterized by their low-resistivity value) which is underlaid by the bodies of igneous rocks, i.e. diorite and andesite (characterized by its high-resistivity value). Based on the comprehensive analysis, there are two aquifers in the study area, they are alluvial deposit and quartz sand deposit. Both of them are unconfined aquifers. The aquifers can be found at the surface to the depth of ±100 m. It can be inferred that the aquifers relatively deepen to the north and east. The quartz sand deposit is a better aquifer since it has better sorting and more-open fabric than the alluvial deposit which provides the deposit a larger capacity for storing and transmitting groundwater.